Adaptive Learning and Returning Adult Online Students - Andrea Gregg; Lynne Johnson (Adult Education Research Conference, 2017)
Many returning adults choose online education for its flexibility but sometimes require additional preparation. We will discuss an adaptive learning pilot to address academic remediation and share preliminary research findings.
Keywords: “adult online learners”; “adaptive learning”